2019
DOI: 10.3390/ani9060346
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Warm Water Improves Growth Performance and Optimizes the Gut Microbiota in Early Postweaning Rabbits during Winter

Abstract: Accumulating evidence indicates that cold exposure changes the composition of the gut microbiota and reduces intestinal immunity in early postweaning livestock. However, little is known about the effects of drinking warm water (WW) on gut microbiota during winter. In this study, we investigated the effects of drinking WW in winter on the growth performance and gut microbiota structure of rabbits raised in poorly insulated housing from the early postweaning period (day 46) to the subadult period (day 82). The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 71 publications
1
23
0
Order By: Relevance
“…Consistent with previous studies on gut microbiota in meat rabbits [18,19], we found that phyla Firmicutes, Bacteroidetes, Cyanobacteria, Verrucomicrobia, Proteobacteria, and Tenericutes, and the genera Ruminococcus_1, Christensenellaceae_R-7_group, Ruminococcaceae_ NK4A214_group, Alistipes, Bacteroides, and Akkermansia were the most dominant microbial taxa in the gut microbial communities irrespective of breed type (Fig. 2).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies on gut microbiota in meat rabbits [18,19], we found that phyla Firmicutes, Bacteroidetes, Cyanobacteria, Verrucomicrobia, Proteobacteria, and Tenericutes, and the genera Ruminococcus_1, Christensenellaceae_R-7_group, Ruminococcaceae_ NK4A214_group, Alistipes, Bacteroides, and Akkermansia were the most dominant microbial taxa in the gut microbial communities irrespective of breed type (Fig. 2).…”
Section: Discussionsupporting
confidence: 91%
“…Due to SCFAs widely participate in physiological and pathophysiological interactions between the gut microbiota and the host [35], we hypothesized that these breed-associated SCFAsproducing species should play a central role in the health, development, and growth of rabbits, and could be considered as potential biomarkers for production performance improvement [36]. Indeed, previous studies have demonstrated that Coprococcus, Ruminococcus, and Lachnospiraceae species are intimately correlated with growth performance of meat rabbits [18,37].…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al reported that changes in the abundance of YS2, Bacteroides, Lactococcus, Lactobacillus, and Prevotella in the gut microbial communities of rabbits were associated with finishing weight (Zeng et al, 2015). Wang Q. et al (2019) found that Coprococcus and Ruminococcaceae_UCG-004 may hinder the production of pro-inflammatory factors that exert beneficial effects on the finishing weight of rabbits. Moreover, North et al (2019) indicated that rabbits with greater abundances of Eubacteriaceae, Natranaerobiaceae, Peptococcaceae, and Syntrophomonadaceae in the gut microbial communities tended to gain more weight at finishing.…”
Section: Introductionmentioning
confidence: 99%
“…Cold stress leads to disruptions of the protective intestinal microflora, reducing the resilience of the rabbits and very probably fostering high mortality rates ( Fortun-Lamonthe & Boullier, 2004 ; Wang et al., 2019 ). Previous studies also stressed the importance of hygiene and proper housing conditions, such as avoiding cold stress, as well as the control of chronic diseases, to prevent intestinal diseases in rabbits (Kowalska et al, 2012; Wang et al., 2019 ). Thus, the feed supplements should be investigated further under optimised conditions, to determine their usefulness in the field.…”
Section: Discussionmentioning
confidence: 99%